2020
DOI: 10.1016/j.jcp.2020.109463
|View full text |Cite
|
Sign up to set email alerts
|

Convergence issues in derivatives of Monte Carlo null-collision integral formulations: A solution

Abstract: When a Monte Carlo algorithm is used to evaluate a physical observable A, it is possible to slightly modify the algorithm so that it evaluates simultaneously A and the derivatives ∂ ς A of A with respect to each problem-parameter ς. The principle is the following: Monte Carlo considers A as the expectation of a random variable, this expectation is an integral, this integral can be derivated as function of the problem-parameter to give a new integral, and this new integral can in turn be evaluated using Monte C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Roger et al [21] have shown that this is always possible, regardless of the parameter type, and even when the parameter affects the integration domain. However, despite being thoroughly general, this proposition can cause practical difficulties in some contexts, in particular as far as numerical convergence is concerned [26].…”
Section: Rejection Samplingmentioning
confidence: 99%
See 3 more Smart Citations
“…Roger et al [21] have shown that this is always possible, regardless of the parameter type, and even when the parameter affects the integration domain. However, despite being thoroughly general, this proposition can cause practical difficulties in some contexts, in particular as far as numerical convergence is concerned [26].…”
Section: Rejection Samplingmentioning
confidence: 99%
“…where ∂ ζ k e is the derivative of k e with respect to ζ (see Lataillade et al [4]). It can be easily seen that − ∂ζ kê k−ke tends towards infinity whenk tends towards k e (for more details, see Tregan et al [26]), that is, when the probability of null collisions decreases. For this reason, the variance of the sensitivity estimator becomes infinite and convergence is impossible.…”
Section: Rejection Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…To carry out the computation, the models are stated in an integral formulation, which is then considered as an expectation, which in turn is estimated by sampling, yielding an unbiased estimate of the expectation as well as its confidence interval. Considering sensitivities, a well-known advantage of the Monte-Carlo method is its ability to estimate such expectation and its derivatives by using the very same sampling, avoiding additional computation time [1,11,14,[17][18][19]26] . This advantage has however some limitations when sensitivity to geometrical parameters is considered because the integral formulation of the model raises formalization and implementation difficulties [25] .…”
Section: Introductionmentioning
confidence: 99%